Are Islamic Values Reduced and Dramatised in Memories of the Alhambra? - Nurhalisa; Nurhakki; Hayat, Nahrul; Iskandar; Wahyuddin; Marta, Rustono Farady (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2024)
This study aims to explore the plot and analyse the Islamic values in the Korean drama Memories Of The AlHambra and how they are displayed in the drama. The study method applies descriptive qualitative, with a semiotic analysis approach from Roland Barthes. The study results show that the drama Memories Of The AlHambra in denotation meaning, which tells a game created to find the lost game master with various conflicts. The connotation meaning is that these two characters have their own habits, a very high ambitious spirit related to the development of their company, J-One Holdings. The myth in this scene is very pro and con because many say religion should not be